Effect of carbon impurity on the dislocation climb in epitaxial GaN on Si substrates. (1st October 2022) - Yang, Xuelin; Shen, Jianfei; Cai, Zidong; Chen, Zhenghao; Shen, Bo
Abstract: We investigate the effect of C doping on dislocation behaviors in GaN grown on Si substrates. A moderate C doping can promote dislocation climb and reduce the dislocation density. With further increasing the C concentration, the dislocation density will increase. In addition, C doping has more influence on edge dislocation than screw dislocation. The stress evolution in the GaN layer is also investigated and the result is consistent with the dislocation behaviors. We thus suggest a mechanism in that C impurities are incorporated into different lattice locations in GaN with increasing the doping level, which can explain the dislocation behaviors.